THE EFFECT OF THE PROBLEM BASED LEARNING MODEL ON STUDENT LEARNING OUTCOMES IN FPB AND KPK MATERIALS IN GRADE IV SDN 1 PAYA DAPUR SOUTH ACEH - Haliza, Mulyati; Vitoria, Linda; Mislinawati, Mislinawati (Elementary Education Research, 2025)
In Mathematics learning, especially in FPB and KPK material, there are problems that cause low learning outcomes because the implementation of the learning process implemented by teachers is still conventional, namely teacher-centered learning. The use of learning models during the teaching and learning process is very important because by using the right learning model students can get better learning outcomes. This research aims to determine the significance of the influence of the PBL model on student learning outcomes in FPB and KPK material in class IV SDN 1 Paya Dapur Aceh Selatan. The approach used in this research is a quantitative approach. The type of research used is an experimental design, namely One Group Pretest-Posttest. The population in this study were all class IV students at SDN 1 Paya Dapur, totaling 18 students. The sample in this research was class IV of SDN 1 Paya Dapur, totaling 18 students. This research was conducted in 4 meetings. The data collection technique used was to provide 5 pretest and posttest questions in essay form. The data analysis technique uses the help of a computer program, namely SPSS Statistics version 16. The data can be tested using a paired t-test (Paired Sample t Test) with the hypothesis Sig 0.05 then Ho is accepted, and if Sig 0.05 then Ho is rejected. Based on the statistical calculation results of the paired t-test, tcount is -8.928 and Sig 0.000. From this comparison, the decision was made that Ha was accepted and Ho was rejected. This means that it is stated that there is an influence of the Problem Based Learning model on student learning outcomes in FPB and KPK material in class IV SDN 1 Paya Dapur Aceh Selatan